Tax performance and reform in the Organization of Eastern Caribbean States (OECS) (UN ECLAC Port of SpainTT, 1999)
Discusses the salient features of the OECS economies and recent economic peformance in these island states. Focuses on some issues relating to saving and investment. Outlines and evaluates the tax systems in the OECS. Includes a discussion on tax revenue and trade policy reforms.
Keywords: TAX SYSTEMS